Prevalence of dysmenorrhea in university students and its relation to school absenteism, physical exercise and use of medicines - Janaina Mayer de Oliveira Nunes; Jessica do Amaral Rodrigues; Mara Suellem de Freitas Moura; Sávia Rene Cavalcante Batista; Susan Karolliny Silva Fontenele Coutinho; Fuad Ahmad Hazime; André Luiz dos Reis Barbosa (Universidade de Fortaleza, 2014)
Objective: To determine the prevalence of dysmenorrhea in female university students and the frequency of school absenteeism, physical exercise and use of medicines to treat the syndrome. Methods: This is a cross-sectional study conducted with university students using a self-administered questionnaire containing sociodemographic, obstetrical, and gynecological data. The menstrual pain was assessed by the visual analogue scale (VAS). Frequency, percentage, mean, and standard deviation were used for descriptive data analysis. Results: The sample consisted of 130 women aged between 17 and 33 years (20.6 ± 2.7 years). One hundred and twenty four volunteers (95.4%) complained of dysmenorrhea. Regarding the intensity, most of the volunteers felt moderate or severe menstrual cramps (51.6% and 36.3%, respectively). Sixty (48.4%) participants reported school absenteeism due to menstrual pain and none of them experienced mild pain. Among the volunteers who had moderate or severe dysmenorrhea, only 24 (20.2%) practiced physical exercise and most of them (79%) needed medicines to treat this syndrome. Conclusion: There was a high prevalence of dysmenorrhea among the university students, and in most cases, the pains limit activities and accounts for school absenteeism. Most women with moderate to severe dysmenorrhea do not practice physical exercise and need to use medicines to treat this syndrome. doi:10.5020/18061230.2013.p381